Nanopesticides: A Systematic Review of Their Prospects With Special Reference to Tea Pest Management - Deka, Bhabesh; Babu, Azariah; Baruah, Chittaranjan; Barthakur, Manash (Frontiers in Nutrition, 2021)
Background: Tea is a natural beverage made from the tender leaves of the tea plant (Camellia sinensis Kuntze). Being of a perennial and monoculture nature in terms of its cultivation system, it provides a stable micro-climate for various insect pests, which cause substantial loss of crop. With the escalating cost of insect pest management and increasing concern about the adverse effects of the pesticide residues in manufactured tea, there is an urgent need to explore other avenues for pest management strategies. Aim: Integrated pest management (IPM) in tea invites an multidisciplinary approach owing to the high pest diversity in the perennial tea plantation system. In this review, we have highlighted current developments of nanotechnology for crop protection and the prospects of nanoparticles (NPs) in plant protection, emphasizing the control of different major pests of tea plantations. Methods: A literature search was performed using the ScienceDirect, Web of Science, Pubmed, and Google Scholar search engines with the following terms: nanotechnology, nanopesticides, tea, and insect pest. An article search concentrated on developments after 1988. Results: We have described the impact of various pests in tea production and innovative approaches on the use of various biosynthesized and syntheric nanopesticides against specific insect pest targets. Simultaneously, we have provided support for NP-based technology and their different categories that are currently employed for the management of pests in different agro-ecosystems. Besides the broad categories of active ingredients (AI) of synthetic insecticides, pheromones and natural resource-based molecules have pesticidal activity and can also be used with NPs as a carriers as alternatives to traditional pest control agents. Finally, the merits and demerits of incorporating NP-based nanopesticides are also illustrated. Conclusions: Nanopesticides for plant protection is an emerging research field, and it offers new methods to design active ingredients amid nanoscale dimensions. Nanopesticide-based formulations have a potential and bright future for the development of more effective and safer pesticide/biopesticides.